2019
DOI: 10.1016/j.bbmt.2019.03.016
|View full text |Cite
|
Sign up to set email alerts
|

A Phase I/II, Open-Label, Prospective, Multicenter Study to Evaluate the Efficacy and Safety of Lower Doses of Bortezomib Plus Busulfan and Melphalan as a Conditioning Regimen in Patients with Multiple Myeloma Undergoing Autologous Peripheral Blood Stem Cell Transplantation: The KMM103 Study

Abstract: +1 relative to the day of autologous stem cell transplantation (ASCT) to a conditioning regimen with busulfan and melphalan (BuMel; 3.2 mg/kg/day busulfan on days -5 to -3 and 140 mg/m 2 /day melphalan on day -2) in patients with multiple myeloma (MM) following bortezomib-based induction chemotherapy. In phase I, doses of bortezomib (.7, 1.0, and 1.3 mg/m 2 ) with BuMel were administered to groups of 3 patients each. No dose-limiting toxicities were observed. The maximum tolerated dose of bortezomib was 1.3 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…Bmib is mainly used as a therapeutic agent for refractory multiple myeloma in hematology clinic, due to its potent anti-tumor activity and yet-unknown biological function (16). It has been reported that Bmib caused the high incidence of neutropenia and stomatitis (17), peripheral neuropathy (18) and epidermal necrolysis (19). We also found potent cytotoxicity of Bmib against OSCC cell lines as well as normal oral cells, especially oral keratinocytes.…”
Section: Discussionsupporting
confidence: 50%
“…Bmib is mainly used as a therapeutic agent for refractory multiple myeloma in hematology clinic, due to its potent anti-tumor activity and yet-unknown biological function (16). It has been reported that Bmib caused the high incidence of neutropenia and stomatitis (17), peripheral neuropathy (18) and epidermal necrolysis (19). We also found potent cytotoxicity of Bmib against OSCC cell lines as well as normal oral cells, especially oral keratinocytes.…”
Section: Discussionsupporting
confidence: 50%
“…For conformation of this, a further randomized, well-controlled trial is needed. In a previous multicenter autoSCT study performed in Korea (KMM 103 study), 3/41 patients (7.3%) experienced mortality within one year due to sepsis in patients who were treated with autoSCT following bortezomib-based induction chemotherapy [30]. Although this study showed relatively lower NRM compared with our study, considering that this study only included newly diagnosed MM patients, it may be a comparable outcome.…”
Section: Discussionmentioning
confidence: 43%
“…Our results however seem better than other recent reports given the lack of maintenance therapy received by patients on our study, perhaps owing to the use of bortezomib in the combination and the PK dosing of the busulfan. To our knowledge, only one other group has prospectively evaluated BuMelVel as a high dose regimen for MM [17] with a much shorter reported follow up of only 31.4 months. In their phase I/II study following a bortezomib based induction, they reported a higher response rate than ours with Table 4.…”
Section: Discussionmentioning
confidence: 99%
“…Blanes et al [26] , [17] BBMT 2019 [18] BBMT 2018 Per high dose arm, pending Barta et al [28] , CLML 2017 83% of patients achieving a very good partial response (VGPR) or better but an inferior median PFS of only 26.8 months and two year PFS of just 56%. Interestingly, they reported less grade III mucositis (only 14.6%) even in the absence of palifermin and no SOS.…”
Section: Progression Free Survival Toxicitymentioning
confidence: 99%